Reverse Logistics in the Amazon: A Territorialized Conceptual Model and Guidelines for Regional Public Policies - Souza, Maria José Feitoza de; Maritan, Franciele Bender; Silva, Jhennifer Lauanne Tavares da Cruz; Soliani, Rodrigo Duarte (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
The implementation of reverse logistics (RL) in Amazonian regions unfolds under institutional, operational, and social conditions that differ significantly from other contexts, influencing the feasibility of circular economy strategies. These territories are characterized by long distances, dispersed small municipalities, reliance on river transport routes, low institutional density, and marked socioeconomic vulnerability, which increase logistical costs and hinder coordination among actors. Despite conceptual advances in the field, analytical models capable of integrating these territorial specificities into RL arrangements remain limited. This article seeks to understand how territorial and institutional factors in the Southwestern Amazon shape the implementation of RL and, based on this analysis, to propose a territorialized conceptual model to guide public policies in peripheral contexts. The research adopts a qualitative, exploratory, and analytic approach, combining a systematic literature review, which resulted in the selection of 33 articles, with a documentary analysis of legal frameworks and management reports from the state of Acre covering the period from 2020 to 2024. The triangulation of theoretical, normative, and institutional evidence enabled the identification of recurrent analytical categories, subsequently organized into six dimensions and three integrated levels — structural, operational, and social, which underpin the proposed conceptual model. The results reveal that RL in the region is shaped by fragile institutional coordination, infrastructure limitations, low flow traceability, dependence on external funding, and restricted productive inclusion of waste pickers. Building on this diagnosis, the study presents a set of key performance indicators and structured guidelines to support the regional implementation of RL, encompassing governance, financing, infrastructure, organic waste valorization, and social participation. The territorialized conceptual model contributes by offering an integrated interpretation of RL in Amazonian states and by providing analytical and operational instruments to inform state plans, waste management policies (PEGIRs), and public policies aimed at circular economy initiatives and sustainable territorial reorganization.